1
$\begingroup$

Consider the quadratic equation $(a+c-b)x^2 + 2cx + b+c-a = 0 $ , where a,b,c are distinct real numbers and a+c-b is not equal to 0. Suppose that both the roots of the equation are rational . Then a) a,b, and c are rational

b)$c/(a-b)$ is rational

c)$b/(c-a)$ is rational

d)$a/(b-c)$ is rational

My attempt - I used the discriminant method to find out the possible roots of the given equation. Which for me came out to be $(-2c + a-b)/(2a -2b +2c)$ and $ ( -2c + b - a)/(2c + 2a - 2b )$

Hence according to me option a is the correct answer , while the correct answer which is given is b. Please tell me where am I going wrong , or what am I missing ?

$\endgroup$
  • $\begingroup$ You did not write an equation, because I don't see the $=$. Anyway, if your equation is $(a+c-b)x^2 +2cx+b+c-a =0$, then your solutions are both wrong. Because the roots are $-1$ (this is easy to check) and $(a-b-c)/(a-b+c)$. Are you sure you copied the text of the problem correctly ? $\endgroup$ – Giovanni Resta Mar 24 '16 at 10:12
1
$\begingroup$

Notice that your polynomial $$(a+c-b)x^2 +2cx +(b+c-a) = (a+c-b) (x - \alpha)(x - \beta) =$$ $$=(a+c-b)x^2 - (a+c-b)(\alpha + \beta) x + (a+c-b)\alpha \beta$$ where $\alpha, \beta$ are the rational roots.

Now, the coefficient of $x$ must be equal $$2c = -(a+c-b)(\alpha + \beta)$$ and with some algebra you get $$\frac{c}{a-b} = -\frac{\alpha + \beta}{\alpha + \beta +2} \in \Bbb{Q}$$

$\endgroup$
  • 1
    $\begingroup$ Notice that you have information only about $a-b$, without any information about $a,b$. I mean, if you call $a= \pi$, $b= 1+ \pi$, their difference is rational, but these are not rational. $\endgroup$ – Crostul Mar 24 '16 at 10:14
1
$\begingroup$

Note that, when $x=-1$, we get $$ (a+c-b)-2c+(b+c-a)=0 $$ so $-1$ is a root for every choice of the parameters $a$, $b$ and $c$. Even if $a+c-b=0$, that would give $c/(a-b)=-1$.

This leads into checking option b. So, suppose $a+c-b\ne0$. The factorization of the polynomial is $$ (x+1)\bigl((a+c-b)x+c-a+b\bigr) $$ so the second root is $$ \frac{(a-b)-c}{(a-b)+c}=\frac{1-\dfrac{c}{a-b}}{1+\dfrac{c}{a-b}} $$ If this is to be rational, also $c/(a-b)$ is rational.

$\endgroup$
1
$\begingroup$

We know that your two roots are rational: $$ r_1 = \frac{-2c + (a - b)}{2(a - b + c)} \in \mathbb Q \qquad\text{and}\qquad r_2 = \frac{-2c - (a - b)}{2(a - b + c)} \in \mathbb Q $$ Hence, their sum and difference are also rational: $$ r_1 + r_2 = \frac{c}{a - b + c} \in \mathbb Q \qquad\text{and}\qquad r_1 - r_2 = \frac{a - b}{a - b + c} \in \mathbb Q $$ But then their quotient is also rational: $$ \frac{r_1 + r_2}{r_1 - r_2} = \frac{c}{a - b} \in \mathbb Q $$

$\endgroup$
1
$\begingroup$

The roots are

$$\frac{-2c\pm \sqrt{4c^2 - 4(c+(a-b))(c-(a-b))}}{2(a+c-b)}$$

$$=\frac{-c\pm (a-b)}{a+c-b}$$

$=\frac{a-b-c}{a-b+c}$ or $\frac{-a+b-c}{a-b+c}=-1$

For the first root,

$$=\frac{a-b+c-2c}{a-b+c}=1-\frac{2c}{a-b+c}$$

So $\frac{2c}{a-b+c}$ is rational, so its inverse is also rational

$\frac{a-b+c}{2c}=\frac{a-b}{2c}+\frac 1 2$

$\endgroup$
0
$\begingroup$

Reduce this to a monic form:

$$ x^2+\frac{2c}{a+c-b}x+\frac{b+c-a}{a+c-b} $$

then as the roots are rational so are the sum and product of the roots, so both $\frac{2c}{a+c-b}$ and $\frac{b+c-a}{a+c-b}$ are rational and so $\frac{c}{b+c-a}$ is also rational, and you should be able to take it from there.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.